PADDY FIELD LAND CHANGE ANALYSIS BASED ON GEOGRAPHY INFORMATION SYSTEM AND REMOTE SENSING IN THE KUBU RAYA DISTRICT - Ekawati Ekawati; Rahmatullah Rizieq; Hardi Dominikus Bancin; Ellyta Ellyta; Ajun Purwanto (Universitas Sebelas Maret (UNS), 2025)
Rice plays an important role in ensuring food security worldwide, especially in Southeast Asia and Indonesia. This study aims to determine the changes in paddy field area and spatial distribution of changes in 2019-2024 using Geographic Information Systems and Remote Sensing in Kuburaya Regency. The data used in this study include the area of paddy fields in Kubu Raya Regency in 2019-2024, an Indonesia Biomass Image, and a Topographic map. The data obtained were then processed using ArcGIS Pro software. Data analysis used a geoprocessing tool with the clip, Intersect, and Dissolve tools and Spatial Analysis using the Map Algebra Tool. The study results showed that overall changes in paddy field area from 2019-2023 were 9036,88 ha. Of the fourteen villages in the Teluk Pakedai sub-district, eight villages experienced an increase in area. The villages are Sungai Nibung, Kuala Karang, Seruat Satu, Tanjung Bunga, Teluk Pakedai Hulu, Madura, Sungai Nipah, and Teluk Pakedai Satu. Overall, the eight villages experienced an increase in the paddy field area of 578.94 ha or 21% of the total area in 2024. Two villages, namely Sungai Nibung and Kuala Karang experienced a 100% increase from 2019. The Geographic Information System and Remote Sensing provide convenience in monitoring and analyzing changes in land use, in this case, changes in the area of paddy fields. Therefore, in the future, this technology will be more effective in its use, because with this technology the data will be easy to update.